Empowerment of Tourism Awareness Groups in Realizing Timpik Tourism Village - Muarifuddin, Muarifuddin; Sungkowo Edy Mulyono; Woro Apriliana Sari; Anisya Pratama Ningsih; Rama Dirga Dwi Sakti; Chairunnisa Asmawi; Triyono, Triyono (Jurnal Abdimas, 2025)
The development of tourism areas is an option that is expected to strengthen both economic potential and conservation efforts. The development of tourism areas is carried out through an integrated transformation of various natural and biological opportunities and assets. All of this requires the ability of the human resources in it. Therefore, this community service program is very much needed to optimize the Timpik Village Pokadarwis in increasing its potential as a tourist village area. Timpik Village is the largest village in Susukan District with beautiful natural panoramas of rice fields and hills with fertile soil types. In addition to potential natural resources, there are also human resources who have a high spirit to advance their village. The various cultures and arts that already exist add their own local wisdom value with the formation of the Tourism Awareness Group (Pokdarwis). However, behind all that, Pokdarwis has not been able to develop the existing tourism potential. Therefore, various mentoring actions are needed in creating a profile of the arts and culture owned by Timpik Village as local wisdom, optimizing the management of village social media, optimizing the use of tourist attractions, and developing the results and marketing of Timpik Village UMKM products.